Cytokines as Therapeutic Targets for the Gastrointestinal Manifestations of Scleroderma - Jennifer M Raoul; Monica Verma; Ernest Tan; Theresa C Peterson (Canadian Journal of Gastroenterology)
Systemic sclerosis (SSc), or scleroderma, is a connective tissue disorder characterized by progressive fibrosis of the skin and internal organs. It has significance for gastroenterologists because the gastrointestinal tract is involved in 90% of SSc patients, who often present with esophageal dysfunction. Though the exact pathogenesis of SSc is unknown, there is increasing evidence supporting an immune mechanism. Cytokines are the soluble mediators of immune activation, altered fibroblast proliferation and extracellular matrix accumulation in SSc and thereby provide important therapeutic targets. In the present review, the involvement of cytokines in SSc is discussed with particular emphasis on cytokines and growth factors that have been implicated in the disease process and likely play an important role in the gastrointestinal manifestations of scleroderma. The role of cytokines as therapeutic targets in scleroderma forms the basis of this timely review